Reticulated, Hyperchromic Rash in a Striated Pattern Mimicking Atopic Dermatitis and Fungal Infection in a 2-Month-Old Female: A Case of Incontinentia Pigmenti. (19th April 2016) - Poliak, Nina; Le, Alexandre; Rainey, Anthony
Abstract : We present a 12-month-old Hispanic female with a reticulated, hyperchromic rash in a striated pattern appearing on upper and lower extremities and trunk and back since the age of 6 weeks. Over the next 10 months, the rash persisted. The rash did not respond to treatment with antifungals and steroids. During her 6-month wellness visit, the patient was diagnosed with incontinentia pigmenti (IP), a rare X-linked dominant disorder, fatal to male fetuses in utero. IP can lead to serious neurological and ophthalmologic consequences. Early diagnosis by primary care physicians and parental education about the condition are essential for prevention of retinal detachment, developmental delay, and dental abnormalities.